Post Colonialist Features of Lorraine Hansberry’s Les Blancs From the Viewpoint of Henry Louis Gates - Maryam Jalali Farahani; Fazel Asadi Amjad; Mohsen Hanif; Tahereh Rezaei (Acta Poética)
Henry Louis Gates has taken Saussure’s term “signifying” and redefined it as a linguistic wordplay which postpones the delivery of meaning and believes in “double-voicedness”, this means to speak both the language of the dominant culture and that of the subordinated one. He also asserts “double-voicedness” as the epitome of “Signifyin (g)”. This paper intends to apply the notions of “Double-voicedness” and “Signifyin (g)” on the manuscript of Les Blancs, written by Lorraine Hansberry, and highlights the anti-colonial aspects of the play.